Tracing family agency in Alick Macheso’s selected songs - Vimbai Moreblessing Matiza-Mtombeni (Taylor and Francis Group, 2022)
The article seeks to highlight family agency in selected songs by Alick Macheso. Family is a vital and respected institution in African societies. As the first locus of development, the family provides nourishment to the individual and sets the conditions for growth. This nurturing and inculcation are done through responsibilities and roles that are designated to different family members in their right capacity to do so. In this regard, musicians as social commentators have an obligation to speak and direct their communities in the right direction. Musicians remind their communities of the existence of a family and give it its unique power as a common place for being united. This article, therefore, seeks to trace family agency in selected Alick Macheso songs in Shona that emphasise the active roles of different family members for a common cause of family unity. Using content analysis of the selected songs, the article is informed by the Afrocentric principle of agency which calls for the African people to be goal setters and achievers. Africana womanist theory is used to guide the discussions in this article. It is important to take note that the analysis focuses on the Shona people of Zimbabwe as reflected in the songs. The article argues that Alick Macheso’s songs here selected bring out family agency as informed by the circumstances and experiences from the community in which they evolve.